Indonesian Exchange Traded Fund Performance - Arianto, Radityo Fajar; Supratikno, Hendrawan; Ugut, Gracia Shinta S.; Hulu, Edison (Budapest International Research and Critics University, 2021)
This study aims to examine the effect of index volatility, changes in market capitalization, volume, momentum and liquidity on the difference between net asset value (NAV) return with the benchmark indexreturn of ETFs in Indonesia individually. The sample from this study amounted to 19 ETFs with purposive sampling method for the period 1 January – 30 June 2020. The analytical tool used was multiple regression with time series data. The results of this study include that the volatility of the benchmark index is a significant factor for the six sample ETFs. Meanwhile, changes in market capitalization are not a significant factor affecting tracking error.